Market-ready innovation is selected for value chain orchestration targeting 17 million smallholders, influencing public-private development agendas, and providing a vehicle for hyperlocal risk control services - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
By embedding research inside an African SME, CCAFS supported the emergence of phygital agriculture and agCelerant, world’s first automated service ecosystem for smallholder plot monitoring from space and ground. “Market-ready, noteworthy of market-creation potential” (European Commission Innovation Radar), selected by the Islamic Development Bank and endorsed by Nigeria to connect 17 million smallholders to value chain stakeholders, it also co-produced “Hyperlocal Elicitation and Understanding of Risks to Stability In Complex Systems” (HEURISTICS), the first instance of CGIAR financing by DARPA.